Post-Disaster Recovery Process Based on Social Resettlement Model - Oman Sukmana (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
Lapindo mudflow disaster in Sidoarjo has caused a tremendous impact for the community, especially in the region of Porong and surrounding areas, not just the impact in the form of the destruction of the physical-ecological environmentbut also the social environment. In disaster management, disaster management conducted through four phases, namely: mitigation preparedness, emergency response, and recovery. The recovery phase includes rehabilitation and socialreconstruction. This study aims to examine how efforts performed in the recovery phase post Sidoarjo mud disaster based on the model of social resettlement. It found that the Sidoarjo mudflow disaster recovery phase included social rehabilitation process consisting three programs, namely social assistance, protection and recovery. Social reconstruction effort postdisaster resettlement consisting three social models, namely model of full social resettlement, mix-social resettlement, and free social resettlement. The model of full social resettlement was the best model and fit reconstruction and social rehabilitation of post-disaster.